2016
DOI: 10.1186/s12868-016-0246-y
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin treatment prior to pentylenetetrazole-induced seizures downregulates the expression of il1b and cox2 and decreases seizure-like behavior in zebrafish larvae

Abstract: Background: It has been demonstrated that the zebrafish model of pentylenetetrazole (PTZ)-evoked seizures and the well-established rodent models of epilepsy are similar pertaining to behavior, electrographic features, and c-fos expression. Although this zebrafish model is suitable for studying seizures, to date, inflammatory response after seizures has not been investigated using this model. Because a relationship between epilepsy and inflammation has been established, in the present study we investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 38 publications
2
20
0
3
Order By: Relevance
“…We previously reported that cox2b mRNA expression was upregulated after PTZ-induced seizures in 7 dpf zebrafish larva (37). To determine whether the cox1 transcription is affected following PTZ-induced seizure, we used real-time qPCR to measure the relative quantification of the cox1 gene.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously reported that cox2b mRNA expression was upregulated after PTZ-induced seizures in 7 dpf zebrafish larva (37). To determine whether the cox1 transcription is affected following PTZ-induced seizure, we used real-time qPCR to measure the relative quantification of the cox1 gene.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed experimental procedures have been described previously (37). Briefly, 7 days post fertilization (dpf) larvae were placed in a 24-well plate (one larva per well) containing 15 mM PTZ [seizure group (SG)] or PTZ-free water [control group (CG)] for 60 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To facilitate a better understanding of epilepsy, zebrafish models of epilepsy have been created by administering pentetrazol to induce seizures (Table 1D). Studies that utilize this method have investigated potential therapeutic compounds to alleviate seizure states as well as to understand changes in gene expression due to seizure events (Barbalho et al 2016; Li et al 2015; Siebel et al 2015). PD is a neurodegenerative disease that results from the loss of dopaminergic cells in the brain (Beitz 2014; Pienaar et al 2010).…”
Section: Zfin As a Resource For Zebrafish Translational Researchmentioning
confidence: 99%